Effect of Capsicum grossum L. and Allium cepal L. Juice on some bacterial species isolated from contamiinated vegetable salad (Baghdad Science Journal, 2007)
Twenty four bacterial isolates were identified from (10) places for wandering sellers in south Baghdad city (Bayaa garage). They were Staphylococcus aureus (9 isolates), Bacillus subtilis (6 isolates), Salmonella spp. (4 isolates) and Psudomonas aeruginosa (5 isolates).Agar well diffusion method was used to definition sensitivity of the fresh and dried juice of Capsicum grossum L. and Allium cepal L. at different concentrations. The fresh juice had no inhibitory activity against the bacterial isolates in contrast to the fresh juice , dried juice which show marked activity against all bacterial isolates at (30) mg/ml.